Interpreting structural geometry in fold-thrust belts: Why style matters. (September 2018) - Butler, Robert W.H.; Bond, Clare E.; Cooper, Mark A.; Watkins, Hannah
Abstract: Structural interpretation in fold-thrust belts has become reliant on a few idealized geometric models (i.e. fault-bend, fault-propagation and detachment folding) and their quantitative methods for section construction and validation. We couple historical review with selected outcrops to show that there is a substantially greater range of solutions available for interpreting the geometry and evolution of thrust belt structures than implied by these idealized models. Examples are documented, and lessons drawn, from comparing structural interpretations developed in the foothills of the Canadian Rockies with those in the Western Alps. Both show a range of structural geometries with regional variations that reflect variations in the pre-kinematic stratigraphic template. Locally, fold-thrust development can localize on pre-existing structures. Thus consideration of the precursor geology is essential for structural interpretation. Using a case study from the Papuan Fold Belt we show that even with seismic data, assessing the role of basement in structural development can be uncertain. The idealized models offer only a narrow range of possible geometries for constructing cross-sections and developing structural understanding in fold-thrust systems. Failure to consider alternatives, and the inherent interpretation uncertainty, has biased understanding of thrust systems leading in turn to over-optimistic risk assessment and repeated drilling surprises. Graphical abstract: Image 1 Highlights: A range of natural and interpreted fold-thrust structures are presented. Changes in structural style are related to pre-existing stratigraphic variations. 2D seismic data can be insufficient to choose between structural interpretations. Idealized fold-thrust models do not adequately represent natural structures. Uncritically adopting idealized models can bias subsurface interpretation.